2021
DOI: 10.3390/rs13081464
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Model Consisting of Supervised and Unsupervised Learning for Landslide Susceptibility Mapping

Abstract: Landslides cause huge damage to social economy and human beings every year. Landslide susceptibility mapping (LSM) occupies an important position in land use and risk management. This study is to investigate a hybrid model which makes full use of the advantage of supervised learning model (SLM) and unsupervised learning model (ULM). Firstly, ten continuous variables were used to develop a ULM which consisted of factor analysis (FA) and k-means cluster for a preliminary landslide susceptibility map. Secondly, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…It continuously improves the prediction accuracy through interactions. A new decision tree was established in the gradient direction of the reducing residuals in each iteration [80]. The basic idea of GBDT is to build several weak classifiers and finally combine them to form a strong classifier after multiple iterations.…”
Section: Gradient Boosting Decision Treementioning
confidence: 99%
“…It continuously improves the prediction accuracy through interactions. A new decision tree was established in the gradient direction of the reducing residuals in each iteration [80]. The basic idea of GBDT is to build several weak classifiers and finally combine them to form a strong classifier after multiple iterations.…”
Section: Gradient Boosting Decision Treementioning
confidence: 99%
“…Peng et al [41] Novel hybrid method combining rough set theory and SVM Yu et al [40] SVM with geographical weighted regression and PSO Pham et al [86] Novel hybrid method using sequential minimal optimization and SVM Zhang et al [117] Fractal dimension with index of entropy and SVM Adnan et al [118] LSM generated by combining the LSM produced by four ML models KNN, MLP, RF, and SVM Wang et al [119] GeoSOM with RF and ensemble ML model consisting of ANN-SVM-GBDT Fang et al [13] Proposed three hybrid models CNN-SVM, CNN-RF, and CNN-LGR Hu et al [48] Combining fractal theory with SVM and NB Rong et al [74] Combination of Bayesian optimization with RF and GBDT Wang et al [55] Integration of MultiBoost with RBFN and CDT Sahana et al [120] Multi-layer perceptron neural network classifier with ensemble ML models like Bagging, Dagging, and DECORATE Xie et al [79] GeoDetector using factor detectors and interaction detectors with four ML models ANN, BN, LGR, and SVM Alqadhi et al [121] Four optimized ML model namely PSO-ANN, PSO-RF, PSO-M5P, and PSO-SVM with LGR Arabameri et al [122] Credal decision tree based hybrid models namely CDT-bagging, CDT-MultiBoost, and CDT-SubSpace Saha et al [123] Hybrid ensemble method using RF as a base classifier and ensemble methods, namely RotFor-RF, RSS-RF, and bagging-RF Xing et al [124] The output of ML models namely back propagation, RF, and SVM are combined using weight factors Hu et al [125] Fuzzy c-means clustering and factor analysis with LGR Zhou et al [51] RF with GeoDetector and recursive feature elimination Sun et al [126] GeoDetector and RF Lui et al [61] GeoDetector with RF Liang et al [71] Combination of unsupervised and supervised ML method Dung et al [127] Novel hybrid method consisting bagging-based rough set and AdaBoost-based rough set Wei et al [128] Spatial response feature with ML classifiers…”
Section: Author Year Hybrid Methodsmentioning
confidence: 99%
“…Nhu et al [42] stated choosing random non-landslide locations using a trial-and-error method has limitations and suggested a more standardized approach for selecting a non-landslide location for future studies. Liang et al [71] used an unsupervised ML model to generate the nonlandslide locations, and the generated dataset was used by supervised ML to generate LSM. The additional process of using an unsupervised ML model for data generation improved the accuracy of the LSM generated by the supervised ML model.…”
Section: Datasets and Landslide Inventorymentioning
confidence: 99%
“…The scoring functions were determined (Equation ( 11)) and LR model was established using five common factors scores (C1-C5) as independent variables. Accordingly, Equation (13) restored the relationship between the 10 conditioning factors and the occurrence of landslides. The coefficients of F1, F4, F5 and F7 were negative, which were not conducive to the occurrence of landslide.…”
Section: Fa Coupled With Lr Modelmentioning
confidence: 96%
“…Traditional machine learning methods (TMLM) as the Logistic regression (LR) model, clustering analysis and principal component analysis have been well verified in LSP [7][8][9]. The new machine learning methods (NMLM), such as support vector machines, artificial neural networks and deep learning, have gained consideration with the development of computer technology [10][11][12][13][14][15][16]. Ensemble learning offers the possibility to further improve the accuracy and reflection of nonlinear relationships between landslide and conditioning factors [17].…”
Section: Introductionmentioning
confidence: 99%